The Concept and content of the terms “land use planning” and “land use management” in Ukraine - Tretyak, A.; Tretiak, V. (Land Management, Cadastre and Land Monitoring, 2017)
Proved that the concept and nature of the terms «land use management» and «land use planning» in Ukraine are not identical. Determined that land use management is the next phase of land use planning, it is a kind of its functional superstructure. Keywords: land use planning, land use management, spatial structure, territorial and functional infrastructure.